2020
DOI: 10.12688/f1000research.22584.2
|View full text |Cite
|
Sign up to set email alerts
|

Computationally going where experiments cannot: a dynamical assessment of dendritic ion channel currents during in vivo-like states

Abstract: Background: Despite technological advances, how specific cell types are involved in brain function remains shrouded in mystery. Further, little is known about the contribution of different ion channel currents to cell excitability across different neuronal subtypes and their dendritic compartments in vivo. The picture that we do have is largely based on somatic recordings performed in vitro. Uncovering dendritic ion channel current contributions in neuron subtypes that represent a minority of the neuronal popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…The models upon which the present work is based have been previously published. Detailed descriptions of these models with equations and parameter values can be accessed from Guet-McCreight and Skinner (33) and Sekulic et al (27). Here we provide a brief description:…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The models upon which the present work is based have been previously published. Detailed descriptions of these models with equations and parameter values can be accessed from Guet-McCreight and Skinner (33) and Sekulic et al (27). Here we provide a brief description:…”
Section: Methodsmentioning
confidence: 99%
“…In parallel, in previous work using I-S3 cell models (32), we had developed an approach for performing high-resolution parameter searches to find excitatory and inhibitory synaptic input parameter combinations that could generate in vivo -like states, and thus create virtual networks from a particular cell’s perspective. We took advantage of this approach to do the same for these new OLM cell models where we demonstrated that h-channel dendritic currents are consistently enhanced during in vivo -levels of synaptic bombardment (33). Importantly, I-S3 cell inputs are a major source of inhibitory synaptic inputs to OLM cells (13) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that using virtual networks, or creating in vivo-like representations with multi-compartment cellular models, as done with our earlier OLM cell models (Sekulić and Skinner, 2017), can lead to insights of circuit function from cellular specifics. Further, we have now used the current OLM cell models to do detailed, dendritic explorations of ion channel dynamics that would not be possible to do experimentally (Guet-McCreight and Skinner, 2020). We have also created in vivo-like states with interneuron-specific interneuron models (Guet-McCreight and Skinner, 2019), and used them to make links between in vitro and in vivo studies (Luo et al, 2020).…”
Section: Limitations and Future Workmentioning
confidence: 99%